RESEARCH OF THE RELATIONSHIP BETWEEN EXISTENTIAL ANXIETY AND THE SENSE OF PERSONALITY’S EXISTENCE (Revista Inclusiones, 2020)
The purpose of the empirical study is to establish relationships between existential anxiety and the sense of personality’s existence (n=60). It is noted that anxiety is the most important element of human existence, the natural reaction of man to uncertainty. A fundamental analysis of the meaning of human existence is presented. The correlation between existential anxiety and the sense of personality’s existence (p≤.05; p≤.01) has been empirically investigated and established, which substantially supplemented the existing knowledge of the studied phenomena. The relationship between the level of the Self-estimation of Personal Anxiety (SPA) and the level of General Awareness of Life (GAL) is stablished and described. The presence of high feedback correlation -.829; p≤.01) was statistically confirmed. The results of the study are summarized and the assumption is made that the awareness of life is a sign of human mental health. It is noted that a high level of anxiety should be considered as a higher possibility of revealing the potential purpose of a person. It is emphasized that living and experiencing one’s existence means learning about the purpose in the world that does not guarantee its comprehension.